Water table depth optimisation solutions to prevent peat fires in the Kapuas River - Rossie Wiedya Nusantara; Urai Edi Suryadi; Tino Orciny Chandra; Ari Krisnohadi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The optimisation of water table management is a significant strategy to prevent the risk of fire and peat subsidence. Peatlands, unique ecosystems, are frequently damaged by drainage due to human activities. The hydrological restoration program aims to protect and manage peat ecosystems, thereby contributing to the enhancement of the resilience of fire-free villages. The success indicators of peat rewetting can be indicated by a shallow water table and a slow rate of subsidence. The objective is to optimise the water table management to prevent fires and subsidence, while increasing community awareness of its importance in agriculture. The implementation of Community Service Activities was conducted in Punggur Kecil Village, involving the Farmer Group in Parit Toom Jaya and the Fire Care Community Parit Rahmat group in the Kapuas River-Punggur Besar River Peat Hydrological Unit. These activities included socialization, educational sessions, and field visits to peatlands to gain insight into the concept of peat rewetting techniques. Practical training was also provided on measuring and monitoring water tables, followed by regular evaluations to assess progress. This strategy not only enhances agricultural productivity but also reduces fire risks and land subsidence, providing a sustainable, long-term solution for peatland ecosystem management.